“A Jornada do Herói” em narrativas sobre professor pesquisador em Ciências Biológicas - Anic, Cinara Calvi (2016)
This research investigates the research perceptions of eight professors of a Biological Sciences undergraduate course, obtained through an oral interview and written training memorial. This is a qualitative research based on the narrative approach, based on the premise of narrating as an opportunity for teachers to reflect on their experiences and experiences, giving them new meanings and meanings and thus constituting a formative activity. The institutional context investigated is the Federal Institute of Education, Science and Technology of Amazonas (IFAM) that offers the course of Degree in Biological Sciences since 2002 and whose Pedagogical Project of the Course (PPP) is guided by the trend professor researcher and development of the reflective teacher . It begins with the narrative of the formative trajectory of the researcher himself to dialogue with the theorists who discuss themes such as the formation for the research, the tendency professor researcher and the role of the narratives as an instrument of formation for the teachers. The "Journey of the Hero", proposed in the 1940s by Joseph Campbell, was chosen as a way of structuring the narrative. The analyzes allowed us to infer aspects that explain the teaching practice of these teachers, who had a technical background and with few experiences in research in Basic Education and initial formation. It was verified that the theoretical, epistemological and methodological consolidation for the training of the researcher professor in the IFAM, especially in the Biological Sciences course, is a process that requires intellectual, institutional investments, discussions and systematized reflection, which can be enhanced by narratives of itself.